2006
DOI: 10.1093/pcp/pci228
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling Identifies Genes Expressed Early During Lint Fibre Initiation in Cotton

Abstract: Cotton fibres are a subset of single epidermal cells that elongate from the seed coat to produce the long cellulose strands or lint used for spinning into yarn. To identify genes that might regulate lint fibre initiation, expression profiles of 0 days post-anthesis (dpa) whole ovules from six reduced fibre or fibreless mutants were compared with wild-type linted cotton using cDNA microarrays. Numerous clones were differentially expressed, but when only those genes that are normally expressed in the ovule outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
152
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 59 publications
2
152
0
1
Order By: Relevance
“…Moreover, A subgenome ESTs of all functional classifications are dramatically enriched in G. hirsutum fiber , a result consistent with the production of long lint fibers in A genome species. Some ESTs have been used to develop sequence-specific markers in breeding and to construct microarrays, leading to the identification of many candidate genes involved in fiber cell initiation and elongation (Arpat et al, 2004;Lee et al, 2006;Shi et al, 2006;Wu et al, 2006;Udall et al, 2007).…”
Section: What Resources Are Available?mentioning
confidence: 99%
“…Moreover, A subgenome ESTs of all functional classifications are dramatically enriched in G. hirsutum fiber , a result consistent with the production of long lint fibers in A genome species. Some ESTs have been used to develop sequence-specific markers in breeding and to construct microarrays, leading to the identification of many candidate genes involved in fiber cell initiation and elongation (Arpat et al, 2004;Lee et al, 2006;Shi et al, 2006;Wu et al, 2006;Udall et al, 2007).…”
Section: What Resources Are Available?mentioning
confidence: 99%
“…The transcriptomes of cotton fibers and that of the fuzzless-lintless (fl) mutant ovules were recently compared; in combination with the results obtained from in vitro ovule culture, the authors proposed that ethylene plays a major role in fiber elongation [25]. Another investigation of 0 DPA ovule transcriptomes of the wide-type and six reduced fiber or fiberless mutants showed that 13 genes were downregulated in mutants, including an MYB transcription factor (GhMyb25) and a homeodomain protein, providing information for parallels between cotton fiber initiation and leaf trichome development [26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on cotton fiber development have been focused largely on gene expression profiles during fiber elongation and secondary cell-wall synthesis (Arpat et al 2004;Shi et al 2006;Udall et al 2006;Wu et al 2006;Yang et al 2006;Taliercio and Boykin 2007). Previous results suggested that transcription factors could play important roles in cotton fiber development.…”
mentioning
confidence: 99%